South-south monetary integration: the case for a research framework beyond the theory of optimum currency area - Barbara Fritz; Laurissa Mühlich (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2007)
Optimum Currency Area (OCA) theory proves inadequate in the analysis of the new regional monetary integration schemes that have sprung up among developing and emerging market economies since the 1990s. Building on the concept of 'original sin' developed by Eichengreen et al. we argue that a different conceptual framework is needed as these regional monetary South-South integration (SSI) schemes differ fundamentally from North-South arrangements because they involve none of the international reserve currencies. Insights from the cases of monetary south-south cooperation in Southern Africa, East Asia and Latin America suggest that SSI can have beneficial effects on macroeconomic stability. This paper sketches a first set of hypotheses on the necessary conditions for these stability gains to materialise.
Keywords: F33; F36; O11; 330; Regional Monetary Integration; Optimum Currency Area (OCA) Theory; Development Theory; ASEAN; MERCOSUR; CMA; Handelsregionalismus; Währungsraum; Währungsunion; Optimaler Währungsraum; Süd-Süd-Beziehungen; ASEAN-Staaten; MERCOSUR-Staaten; Südliches Afrika